(untitled) (Jurnal Matematika, Statistika dan Komputasi, 2025)
Solar irradiance is the process by which radiant energy from the sun reaches the earth. BMKG states that solar irradiance reaches 100% when the sun shines for 8 hours a day. Less than 8 hours of solar irradiance a day can affect local and global climate systems. This research aims to analyze and predict of average sunshine duration in Pasuruan with the Singular Spectrum Analysis (SSA) method. Based on the SSA model for optimal solar irradiation with and Grouping Effect , this study analyzes the prediction of average sunshine duration in Pasuruan which produces a Mean Absolute Percentage Error (MAPE) value of 19.53%. The results indicate that the predictions are effectively categorized for estimating the average solar irradiance. The highest average was in July at 60.1% and the lowest average was in November at 12.82%